Antimicrobial and Efflux Pump Inhibitory Activity of Carvotacetones from Sphaeranthus africanus Against Mycobacteria - Huyen Thi Tran; Julia Solnier; Eva-Maria Pf; Olaf Kunert; Liam Martin; Sanjib Bhakta; Loi Huynh; Tri Minh Le; Rudolf Bauer; Franz Bucar (MDPI AG, 2020)
Carvotacetones (1-7) isolated from Sphaeranthus africanus were screened for their antimycobacterial and efflux pump (EP) inhibitory potential against the mycobacterial model strains Mycobacterium smegmatis mc2 155, Mycobacterium aurum ATCC 23366, and Mycobacterium bovis BCG ATCC 35734. The minimum inhibitory concentrations (MICs) of the carvotacetones were detected through high-throughput spot culture growth inhibition (HT-SPOTi) and microbroth dilution assays. In order to assess the potential of the compounds 1 and 6 to accumulate ethidium bromide (EtBr) in M. smegmatis and M. aurum, a microtiter plate-based fluorometric assay was used to determine efflux activity. Compounds 1 and 6 were analyzed for their modulating effects on the MIC of EtBr and the antibiotic rifampicin (RIF) against M. smegmatis. Carvotacetones 1 and 6 had potent antibacterial effects on M. aurum and M. bovis BCG (MIC ≤ 31.25 mg/L) and could successfully enhance EtBr activity against M. smegmatis. Compound 1 appeared as the most efficient agent for impairing the efflux mechanism in M. smegmatis. Both compounds 1 and 6 were highly effective against M. aurum and M. bovis BCG. In particular, compound 1 was identified as a valuable candidate for inhibiting mycobacterial efflux mechanisms and as a promising adjuvant in the therapy of tuberculosis or other non-tubercular mycobacterial infections.